-5(x+3)-(9x-4)=x-5+3

Simple and best practice solution for -5(x+3)-(9x-4)=x-5+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -5(x+3)-(9x-4)=x-5+3 equation:


Simplifying
-5(x + 3) + -1(9x + -4) = x + -5 + 3

Reorder the terms:
-5(3 + x) + -1(9x + -4) = x + -5 + 3
(3 * -5 + x * -5) + -1(9x + -4) = x + -5 + 3
(-15 + -5x) + -1(9x + -4) = x + -5 + 3

Reorder the terms:
-15 + -5x + -1(-4 + 9x) = x + -5 + 3
-15 + -5x + (-4 * -1 + 9x * -1) = x + -5 + 3
-15 + -5x + (4 + -9x) = x + -5 + 3

Reorder the terms:
-15 + 4 + -5x + -9x = x + -5 + 3

Combine like terms: -15 + 4 = -11
-11 + -5x + -9x = x + -5 + 3

Combine like terms: -5x + -9x = -14x
-11 + -14x = x + -5 + 3

Reorder the terms:
-11 + -14x = -5 + 3 + x

Combine like terms: -5 + 3 = -2
-11 + -14x = -2 + x

Solving
-11 + -14x = -2 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
-11 + -14x + -1x = -2 + x + -1x

Combine like terms: -14x + -1x = -15x
-11 + -15x = -2 + x + -1x

Combine like terms: x + -1x = 0
-11 + -15x = -2 + 0
-11 + -15x = -2

Add '11' to each side of the equation.
-11 + 11 + -15x = -2 + 11

Combine like terms: -11 + 11 = 0
0 + -15x = -2 + 11
-15x = -2 + 11

Combine like terms: -2 + 11 = 9
-15x = 9

Divide each side by '-15'.
x = -0.6

Simplifying
x = -0.6

See similar equations:

| x-10+2x-221+0.5x+5=180 | | z(z-3)+2(z+3)=18 | | 5h+4=4h+11 | | w(20w-73)=-63 | | 6(x^2+x-20)=0 | | 5n+43=-2(1-7n) | | 6y-8=4y+2 | | 7+7x=7+8x | | x+5x+4x-6=180 | | 7=4y-2y+1 | | 3v-5=16 | | z^2-30z+c=0 | | (13b-7)-3(4b+3)=-6 | | 4x-5=(x-1) | | 3.5(x-2)=12-.5x | | -63+8x=173x | | 4x^3-80x^2+400x=500 | | -9x-155=85+3x | | 5x-3=-x+3 | | 10+3x=-5x+98 | | 5b+3=4b-2 | | 6x-4=-4-2x | | 3x+9=2y-4 | | 6m^2+15m+3=0 | | -2x+5=10+4x | | 2x+4=-x-20 | | 22=2y | | 0=x^2+26x+232 | | x+1+2x+2+3x+3+4x=56 | | 2x+7=-x-1 | | 11x-79=47+5x | | 5x-3+2x=2x+2 |

Equations solver categories